2008
DOI: 10.1007/s10832-008-9443-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and dielectric properties of highly oriented BaTiO3 films: Influence of oxygen pressure utilized during pulsed laser deposition

Abstract: The crystal structure of BaTiO 3 thin films grown by pulsed laser deposition on MgO substrates was found to be strongly influenced by the oxygen pressure used during growth. Low pressures produced epitaxial films with highly strained out-of-plane lattice parameter c compared to inplane parameter a, while increasing oxygen pressure resulted in the ratio c/a<1 with a concomitant increase in polycrystallinity. The dielectric properties varied with changing crystal structure reaching a maximum permittivity value i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
8
14
0
Order By: Relevance
“…Dielectric maximum moved toward higher temperatures in 150 nm film as the frequency changed from 100 Hz to 1 kHz and in 200 nm film as the frequency increased from 100 Hz to 10 kHz. Same kind of frequency dependence was also found in highly oriented BaTiO 3 thin films [17]. This temperature shift towards higher temperatures as a function of frequency might be an indication of relaxor behaviour [18,19].…”
Section: Resultssupporting
confidence: 69%
“…Dielectric maximum moved toward higher temperatures in 150 nm film as the frequency changed from 100 Hz to 1 kHz and in 200 nm film as the frequency increased from 100 Hz to 10 kHz. Same kind of frequency dependence was also found in highly oriented BaTiO 3 thin films [17]. This temperature shift towards higher temperatures as a function of frequency might be an indication of relaxor behaviour [18,19].…”
Section: Resultssupporting
confidence: 69%
“…The crystal phase could not be determined conclusively, and this can potentially explain the deviation between birefringence and crystal distortion values in films deposited at 25 and 30 mTorr oxygen pressures. The shift from epitaxial film to polycrystalline structure was also suggested by atomic force microscope (AFM) studies as reported in [7]. The surfaces of the samples deposited at low oxygen pressures (1.5 and 10 mTorr) had RMS roughness of less than 1 nm.…”
Section: Introductionsupporting
confidence: 54%
“…The out-ofplane lattice parameters were calculated from θ−2θ patterns (Rigagu RU 300) while in-plane parameters were determined from (202)/(220) non parallel-to-surface planes (Bruker D8 equipment) together with θ−2θ scan results. Further information on the XRD analysis and surface morphology studies are provided in ref [7]. A Si x N y striploaded waveguide design was chosen for the Mach-Zehnder modulator waveguides, allowing for the use of easily patterned materials for the guiding structure rather than having to pattern the BTO layer itself.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric maximum around ∼420 • C also moved towards higher temperatures with frequency from 100 Hz to 10 kHz. Same kind of relaxor-type dependence was also found in our previous studies on nanocrystalline PNZT films [12], as well as on highly oriented BaTiO 3 [13], and in (Pb 0.5 Ba 0.5 )ZrO 3 thin films studied by Hao et al [14]. The 150-nm-film, for comparison, showed typical diffusive phase transition with one dielectric relaxation maximum around ∼390 • C, and the transition of the 50-nm-film was already strongly suppressed due to high residual compressive stress state.…”
Section: Resultssupporting
confidence: 85%